2016
DOI: 10.1186/s13033-016-0076-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequent callers to telephone helplines: new evidence and a new service model

Abstract: BackgroundThis paper describes a program of work designed to inform a service model to address a challenge for telephone helplines, namely frequent callers.MethodsWe conducted a systematic literature review and four empirical studies that drew on different data sources—(a) routinely collected calls data from Lifeline, Australia’s largest telephone helpline; (b) data from surveys/interviews with Lifeline frequent callers; (c) data from the Diagnosis, Management and Outcomes of Depression in Primary Care (diamon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 33 publications
6
67
1
1
Order By: Relevance
“…The challenge the TNs experienced with FCs in the present study is congruent with the study by Holmström et al (), where FCs constituted a challenge for TNs and often comprised the caller's worries and anxieties. Furthermore, in the background it is described that in several studies the FCs were more likely to have psychiatric comorbidity (Corral et al, ; Edwards et al, ; Fisher et al, ; Liu et al, ; Middleton et al, ; Pirkis et al, ; Ramors‐Rivers et al, ; Spittal et al, ), which also seems to be the case in the present study according to these TNs. It has previously been shown that there is a positive relationship between expressions of concern by the caller and disapproval by the nurse (Ernesäter, Engström, Winblad, Rahmqvist, & Holmström, ).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The challenge the TNs experienced with FCs in the present study is congruent with the study by Holmström et al (), where FCs constituted a challenge for TNs and often comprised the caller's worries and anxieties. Furthermore, in the background it is described that in several studies the FCs were more likely to have psychiatric comorbidity (Corral et al, ; Edwards et al, ; Fisher et al, ; Liu et al, ; Middleton et al, ; Pirkis et al, ; Ramors‐Rivers et al, ; Spittal et al, ), which also seems to be the case in the present study according to these TNs. It has previously been shown that there is a positive relationship between expressions of concern by the caller and disapproval by the nurse (Ernesäter, Engström, Winblad, Rahmqvist, & Holmström, ).…”
Section: Discussionsupporting
confidence: 76%
“…FCs account for a significant proportion of all calls to telephone nursing services (Middleton et al, 2014;Pirkis et al, 2016;Scott et al, 2014). Responding to FCs' calls may also imply that other calls are put on hold for longer than is ideal, hence reducing access.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has classified callers as 'one-off' or 'repeat callers' and studies found that 3% of callers take up 47-60% of the service capacity [3]- [7]. Research on call demand also reported that calls to helplines peak at weekends and in the evening during the week [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, frequent callers might need to be given constraints on the number of calls they can make to the hotline and the length of those calls. A service model was proposed that involved specially training certain call workers to work with frequent callers, who would enforce limitations and work with a caller to establish long-term mental health care that is not the hotline (Pirkis et al, 2016).…”
Section: Frequent Callersmentioning
confidence: 99%